1996
DOI: 10.1097/00006454-199603000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the safety and immunogenicity of a pneumococcal conjugate with a licensed polysaccharide vaccine in human immunodeficiency virus and non-human immunodeficiency virus-infected children

Abstract: We conclude that antibody responses to natural infection, PCV and particularly PPV are poorer in HIV-infected than in non-HIV-infected children. PCV is as safe as and more immunogenic than the currently licensed PPV among HIV-infected and non-HIV-infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 15 publications
2
40
2
1
Order By: Relevance
“…The analysis of these data confirmed our results with the restriction of smaller group sizes (Table 5). This better immunogenicity of PCV compared to PPV beyond infancy has also been suggested elsewhere (21,39). Induction of immunological memory after priming with a pneumococcal conjugate vaccine had previously also been shown for infants and patients with HodgkinЈs disease after treatment (9,15).…”
Section: Discussionmentioning
confidence: 53%
“…The analysis of these data confirmed our results with the restriction of smaller group sizes (Table 5). This better immunogenicity of PCV compared to PPV beyond infancy has also been suggested elsewhere (21,39). Induction of immunological memory after priming with a pneumococcal conjugate vaccine had previously also been shown for infants and patients with HodgkinЈs disease after treatment (9,15).…”
Section: Discussionmentioning
confidence: 53%
“…This lack of response can be overcome by conjugating the polysaccharide to a protein carrier. Several experimental pneumococcal conjugate vaccines have recently been developed (1,2,9,27). We have previously shown that the CRM197-heptavalent pneumococcal conjugate vaccine induced an IgG antibody response in pa-tients with recurrent infections who had failed to mount an adequate response to the polysaccharide vaccine (28).…”
mentioning
confidence: 99%
“…Pneumococcal conjugate vaccines have been shown to be immunogenic among children, including those with HIV infection 67 and efficacy studies in children are in progress in South Africa and The Gambia. Conjugate vaccines may also hold promise for HIV-infected adults and need to be evaluated.…”
Section: Preventing Pneumococcal Diseasementioning
confidence: 99%